Fabrication of bismuth ferrite/graphitic carbon nitride/N-doped graphene quantum dots composite for high performance supercapacitors. (December 2022) - Shalini Reghunath, B.; Rajasekaran, Sruthi; Devi K R, Sunaja; Saravanakumar, B.; William, J. Johnson; Pinheiro, Dephan; Govindarajan, Durai; Kheawhom, Soorathep
Abstract: Supercapacitors are potential energy storage devices with a broad range of applications. In this study, we are investigating a bismuth ferrite/graphitic carbon nitride/N-doped graphene quantum dots composite as an electrode material for supercapacitor applications. XRD patterns of the composite exhibit the different crystalline phases of the individual component and confirm the rhombohedral structure of the composite. The wafer-like structure of bismuth ferrite is produced via hydrothermal technique supported on 2D structures viz. graphitic carbon nitride and N-doped graphene quantum dots. Compared to bismuth ferrite and bismuth ferrite/graphitic carbon nitride (g-CN) binary composite, the bismuth ferrite/g-CN/N-doped graphene quantum dots demonstrates a superior specific capacitance of 1472 F g −1 at 1 A g −1 current density. After 3000 charging-discharging cycles, the device maintains its cycling stability with 87% capacitance retention. A supercapacitor device is assembled utilizing bismuth ferrite/graphitic carbon nitride/N-doped graphene quantum dots and activated carbon as electrodes. This device shows a significantly improved performance with an energy density of 53.1 Wh kg −1 and a power density of 705.4 W kg −1 . As a result, the composite electrode developed in this study is proved to be a potential electrode material for high-performance energy storage devices. Graphical abstract: Image 1 Highlights: BiFeO3 /g-CN/N-doped graphene quantum dot is prepared via a two-step method. Superior specific capacitance of 1472 F g −1 at 1 A g −1 was shown by the composite. The material showed high level of capacity retention of 87% after 3000 cycles. An energy density of 53.1 Wh kg −1 and specific power of 705.4 W kg −1 are exhibited.